2021
DOI: 10.20944/preprints202105.0736.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of Health Awareness in South Korean Middle School Students According to Type of Online Physical Education Classes During the COVID-19 Pandemic

Abstract: This study aimed to assess the differences in the importance and performance of health awareness in Korean middle school students according to the types of online physical education classes they attended during the coronavirus disease-2019 pandemic. Overall, 583 participants were selected using a convenience sampling method; the data were obtained through an online survey using Google forms. Frequency analysis, reliability analysis, independent sample t-test, and importance-performance analysis were performed.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Participants' demographics were set to sex and nationality, both of which were assessed as nominal variables. To measure health perception, the Health Perception Scale developed by Ware [29] and validated by Barakat et al [30], Jones [31], Lee, So, and Youn [5], and Yoo, Han, Youn, and Jung [6] was modified for use in this study. In particular, we used an alternative IPA questionnaire to prevent the results primarily converging in a single quadrant, which is a shortcoming of IPA.…”
Section: Instrumentsmentioning
confidence: 99%
See 3 more Smart Citations
“…Participants' demographics were set to sex and nationality, both of which were assessed as nominal variables. To measure health perception, the Health Perception Scale developed by Ware [29] and validated by Barakat et al [30], Jones [31], Lee, So, and Youn [5], and Yoo, Han, Youn, and Jung [6] was modified for use in this study. In particular, we used an alternative IPA questionnaire to prevent the results primarily converging in a single quadrant, which is a shortcoming of IPA.…”
Section: Instrumentsmentioning
confidence: 99%
“…These problems are not confined to the adult population but rage across adolescents as well [5,6]. Schools-the place where Korean adolescents spend most of their day-are focused on anti-COVID-19 measures to halt the spread of the virus.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The healthy information literacy of this group will directly affect their health level in adulthood, so the middle school stage is also an important period for cultivating healthy information literacy and establishing health-related habits [9]. The global outbreak of COVID-19 has brought some changes to middle school students' living and learning styles in many countries around the world, such as teaching methods [10][11], exercise [12][13], sleep and mental state [14][15] Through the search of domestic and foreign literature databases, no studies have been found on the health information behavior of middle school students and the status of COVID-19 infection after the release of the policy. In this study, a town-level middle school in the southeast of Henan Province was selected as the research object to explore the health information literacy level and infection situation of middle school students after the comprehensive liberalization of the COVID-19, and to provide a basis for precise health promotion and scientific intervention.…”
Section: Introductionmentioning
confidence: 99%